(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The evaluation of food safety in genetically modified (GM) crops is a critical area in agricultural biotechnology. This paper presents a novel approach using effective deep learning techniques for the assessment of GM crops’ safety.